Pengembangan Materi Ajar Menulis Teks Laporan Hasil Observasi Pada Kurikulum Merdeka Fase D Berbantuan Lectora Inspire Pada Siswa Kelas VIII SMP Negeri 1 Bintang Bayu Tahun Ajaran 2023/2024 - Yanti Tamara Ulita Sihotang; M. Oky Fardian Gafari (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The aim of this research is to determine the process of developing teaching materials for observation report texts in the Merdeka phase D curriculum assisted by Lectora Inspire in class VIII SMP and to determine the feasibility of the resulting product. This research uses research and development methods using the Borg and Gall procedure with stages of potential and problems, data collection, product design, product validation, product revision, and limited trials. The feasibility value is calculated using a Likert scale based on the results of material expert validation, design expert validation, and study teacher assessment. The material development process was carried out to add several contributions in developing the existing observation report text material to be better. The research results show that the product resulting from the research "Development of Teaching Materials for Writing Text Reports on Observations in the Merdeka Curriculum Phase D for Class VIII Students of SMP Negeri 1 Bintang Bayu for the 2023/2024 Academic Year" is included in the "Very Good" category. This is based on the results of validation and material experts which were carried out twice with a score of 89% in the "Very Good" category and media expert validation twice with a score of 93% in the "Very good" category. Thus, the product is said to be suitable for use in the learning process.